The First Cut is the Deepest: Repeated Interactions of Coauthorship and Academic Productivity in Nobel Laureate Teams - Ho Fai Chan; Ali Sina Önder; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2015)
Despite much in-depth investigation of factors influencing this evolution in various scientific fields, our knowledge about how efficiency or creativity is linked to the longevity of collaborative relationships remains very limited. We explore what Nobel laureates' coauthorship patterns reveal about the nature of scientific collaborations looking at the intensity and success of scientific collaborations across fields and across laureates' collaborative lifecycles in physics, chemistry, and physiology/medicine. We find that more collaboration with the same researcher is actually no better for advancing creativity: publications produced early in a sequence of repeated collaborations with a given coauthor tend to be published better and cited more than papers that come later in the collaboration with the same coauthor. Thus, our results indicate that scientific collaboration involves conceptual complementarities that may erode over a sequence of repeated interactions.
Keywords: D20; O30; 330; Innovation; Scientific Collaboration; Team Formation; Nobel Laureates